A metabarcoding comparison of taxonomic richness and composition between the water column and the benthic boundary layer. (20th December 2020) - Parry, H E; Atkinson, A; Somerfield, P J; Lindeque, P K
Abstract: Zooplankton monitoring in shelf seas predominantly uses nets that miss the benthic boundary layer (BBL) just above the seabed. However, this boundary between pelagic and benthic assemblages can be faunistically rich, having its own distinct hyperbenthic fauna and acting as a low-light refuge for overwintering or dielly migrating zooplankton. To compare species richness and composition between pelagic and BBL habitats, we sampled a long-term monitoring site in the Western English Channel seasonally. Metabarcoding methods applied to vertical net samples (top 50 m in a ∼54-m water column) and those from a hyperbenthic sledge generated >100 000 sequences clustered into 294 operational taxonomic units. Of these, 215 were found in the BBL and 170 in the water column. Some key taxa (e.g. mysids) were native to the BBL; by contrast, other delicate taxa (e.g. ctenophores) seemed to avoid the BBL. The major contrasts in plankton composition related to the seasonal cycle rather than to pelagic-BBL differences, suggesting that the basic dynamics of the site are captured by our ongoing long-term weekly resolution monitoring. Overall, metabarcoding approaches, applied to both water column and BBL, provide an independent view of plankton dynamics, and augment existing traditional methods.